Gaya Komunikasi Kepemimpinan Situasional Dalam Mengembangkan Kreatifitas Program Acara Di Televisi (Studi Pada GM Production RTV) - Koswara, Nono; Arlena, Wenny Maya; Ahmad, Toni (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
Leadership style is how a leader carries out his duties, functions and responsibilities and how the leader is seen and assessed by the employees he leads, or a group that has observed him indirectly. A leader is able to admit his mistakes to correct them, is of service, enthusiasm to continue learning, able to evaluate an event that has been carried out and provide motivation to all employees. Leadership communication in organizations can be illustrated in ways specific in building innovation within the organization. That being said, because a change or new ways are required a specific way too for subordinates, so that subordinates want to work in a new way by new Hope. So it's not just delivering a message, but invites, obeys, to carry out what is desired leader. These specific communication skills in communication organization is called the communication style. The situational leadership theory developed by Paul Harsey and Kenneth H. Blanchard, the emerging leadership style can take four forms, namely: 1. Telling, 2.